Pleistocene dynamics of dust accumulation and soil formation in the southern Caspian Lowlands - New insights from the loess-paleosol sequence at Neka-Abelou, northern Iran. (1st February 2021) - Kehl, Martin; Vlaminck, Stefan; Köhler, Tina; Laag, Christian; Rolf, Christian; Tsukamoto, Sumiko; Frechen, Manfred; Sumita, Mari; Schmincke, Hans-Ulrich; Khormali, Farhad
Abstract: The southern Caspian Lowland sensitively reacted to Pleistocene climate change and is a key area for reconstructing climate dynamics and landscape evolution in Southern Eurasia. Loess-paleosol sequences (LPS) of the northern foothills of Alborz Mountains provide detailed records of climate-induced changes of dust accumulation and soil formation correlating with relatively dry or moist conditions of the past. The LPS at Neka-Abelou (NA) was studied in detail in order to understand these dynamics and provide a base for regional pedostratigraphic correlation. We have carried out high-resolution analyses of grain-size, sediment color, mass specific and frequency-dependent magnetic susceptibility and carbonate content and established a temporal framework as based on luminescence dating using a post-IR infrared stimulated luminescence (pIRIR) protocol and fading corrections. The LPS of NA is composed of finely textured loess, which is subdivided by at least eleven paleosols. Moreover, it contains a thin loess layer with lenses of trachytic tephra which most likely originated from the Damavand volcano and was deposited during Marine Isotope Stage (MIS) 4. The lower part of the LPS at NA consists of four strongly-developed reddish-brown paleosols (Bt, Btg horizons) separated by thin layers of pedogenically-altered loess indicating moist climate conditions and low dust accumulation rates during the Middle Pleistocene or earlier. The central part contains a pedocomplex of clay-rich paleosols composed of well developed Bt, ABk and Bw horizons formed under strongly reduced dust accumulation rates and intercalated by loess layers. Pedostratigraphic reasoning suggests that this pedocomplex formed during MIS 5, which is corroborated by luminescence dating. The pedocomplex reflects precession time scale climate change and represents an excellent pedostratigraphic marker recognized in numerous exposures along the northern foothills of the Alborz Mountains. The upper part of the LPS accumulated during the Last Pleniglacial and contains probably six weakly developed synsedimentary paleosols (CBk horizons) as well as the modern soil (Bt horizon). Magnetic susceptibility records show very close similarity with the pleniglacial sequence of the LPS at Toshan located about 100 km farther to the east of the Caspian Lowlands suggesting that the weak paleosols at both locations have formed synchronously, which is supported by luminescence dating. Their presence thus reflects at least a regional-scale climate change between dry phases and those of slightly increased edaphic moisture with ongoing dust supply. The LPS of the Caspian Lowlands document a multitude of changes between dominance of dust accumulation or pedogenesis controlled by moisture availability in the context of Pleistocene climate change. The proposed regional pedostratigraphy for the Late Quaternary provides a scheme for large-scale stratigraphic correlation and reconstruction of climate change in Southern Eurasia. Highlights: Loess in Northern Iran sensitively reacted on Pleistocene climate change. Dust accumulation and soil formation followed climate cycles of the Northern Hemisphere. Pedostratigraphic correlation provides link within Southern Eurasian loess belt. Southern Caspian Lowlands provide key area for climate reconstruction in West Asia.